Arazá: Eugenia stipitata Mc Vaught as a Potential Functional Food - Luis Acosta-Vega; Diego A. Moreno; Liceth N. Cuéllar Álvarez (Foods, 2024)
Arazá is a fruit native to the Amazonian region with characteristic properties such as aroma, texture, color, and marked acidity. Additionally, the fruit is rich in bioactive compounds in its three fractions (seed, pulp, and peel), such as ascorbic acid, phenolic compounds (and their derivatives), and carotenoids, which have been extensively investigated in the literature for their beneficial properties for human health. However, it is a little-known fruit, and the role it can play in health-promoting activities related to the treatment and prevention of non-communicable diseases (NCDs) when incorporated into the diet is also unknown. Therefore, it is necessary to know the profile of bioactive compounds and the biological properties Arazá possesses, which is the aim of this review.